Impact of Light at Night Is Phase Dependent: A Study on Migratory Redheaded Bunting (Emberiza bruniceps) - Kumar, Jayant; Malik, Shalie; Bhardwaj, Sanjay Kumar; Rani, Sangeeta (Frontiers in Ecology and Evolution, 2021)
Artificial light at night (LAN) alters the physiology and behavior of the organism; however, very little is known about phase dependent effects of LAN particularly in night migratory songbirds. Therefore, in the present study we investigated whether the effects of LAN on daily activity and photoperiodic responses in Palaearctic Indian migratory songbird, redheaded buntings (Emberiza bruniceps) are dependent on different phases of night. Male buntings maintained under short photoperiod (8L:16D; L = 100 lux, D < 0.1 lux) in individual activity cages were exposed to LAN (2 lux) for 6 weeks either in 4 h bin given at different phases of 16 h night (early, mid or late at ZT08-12, ZT14-18 or ZT20-24 respectively; n = 9 each group), or throughout 16 h night (all night light, n = 6, ZT 08-24, the time of lights ON was considered as Zeitgeber time 0, ZT 0). A group (n = 6) with no LAN served as control. The results showed that LAN at different phases of night induces differential effects as shown by intense activity during night, altered melatonin and temperature rhythms, increase in body mass and body fattening, food intake and gonadal size. Mid night light exposure has greater impact on migration and reproduction linked phenotypes which is similar to the ones that received light throughout night. The highlights of current study are that (i) LAN impacts day-night activity behavior (ii) its continuity with the day alters perception of day length (iii) birds showed differential sensitivity to LAN in phase dependent manner (iv) direction of placing LAN affects the daily responses e.g. LAN in early night was “accepted” as extended dusk but late night was considered as early dawn (v) mid night LAN was most effective and induced similar responses as that of continuous LAN. Over all, light at night induces long day responses in short days and shows differential sensitivity of different phases of night towards light. This information may be valuable in adopting part-night lighting approach to help reduce the physiological burden such as early migration and reproduction, of artificial lighting on the nocturnal migrants.